Ventilação em pronação na síndrome do desconforto respiratório agudo: revisão integrativa da literatura - Escobar, Carla Teles (Universidade do Vale do Rio dos Sinos, 2011)
The Acute Respiratory Distress Syndrome (ARDS) is a significant cause of morbimortality in intensive care units, and has no specific pharmacological treatment. The prone position is proposed to improve oxygenation in patients with ARDS, requiring observant and skilled nursing care assistance. The purpose of this integrative review of literature is to examine the mechanisms, benefits, complications and methods of the prone position in ARDS patients. The search of the articles was made in the databases LILACS, SIELO, and MEDLINE in the period of 2000 to 2010, with the descriptors ventilation and prone, prone decubitus, prone and nursing, acute respiratory distress syndrome and prone, SARA and prone. Twenty-two articles were reviewed. Among the results found, it has been identified that there are beneficial effects on the prone position in relation to oxygenation and respiratory mechanics. There is no consensus regarding the type of patient who would benefit from such a maneuver, what is its effectiveness on the patients' survival and what is the ideal time of pronation. The technique proved to be safe when applied with a trained staff. The most common adverse reactions are pressure ulcers and accidental extubation. It has been concluded that there is still much research needed to better define the effect of pronation in patients, especially those with ARDS, since its use is not recommended in all cases.
Keywords: Ventilação e prona; Posição prona; Posição prona em pacientes com Síndrome do Desconforto Respiratoria Aguda ( SDRA); Síndrome da angústia respiratória aguda (SARA); Enfermagem; Ventilation and prone; Prone position; Prone position in patients with acute respiratory distress syndrome (ARDS); Acute respiratory distress syndrome (ARDS); Nursing